PENGARUH PEMBINAAN DAN KOORDINASI INTERNAL ALUMNI TERHADAP EFEKTIVITAS KERJA ASMTB BANDUNG - Mulyaningsih (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2019)
This research is originated from the main problem that is, the lower organizational effectiveness. Human is the main factor in gaining an organization's success to achieve its objectives. In line with the position of ASMTB alumni in determining the success of the college and the implementation of human resources, there are problems and challenges that must be faced. The alumni of ASMTB require coaching and internal coordination to achieve effectiveness. It was found that the effectiveness of alumni performance is still low and it can be inferred from the existence of the alumni who are less concerned about ASMTB and the alumni who do not register as alumni because until now it is only 10% graduates were involved in the alumni tresshold. The problem indicators appear caused by internal coaching and coordination that has not been implemented optimally. The results show that there is a simultaneous effect of 47.3% regarding the internal coaching and coordination. Testing indicates that the partial effect on the variance of coaching effectiveness of 21.2% and a partial internal coordination variables influence the effectiveness of the work which is determined by 24,2%.